Development of a Functional Software Test Model Based on the SELENIUM Tool - Chinarro Morales, Evelyn (2017)
This project focuses on presenting a reference model based on tools already created to automate the process of performing functional tests during the evaluation of the quality of the developed product. This automation includes the evaluation of certain automated test management tools and automated functional testing.Software development and computer provide quality service is what is currently achieved with functional tests made in the development stage. This process is very important and critical part in the development process and must be done with greater efficiency and better efficiency. During the project the current processes that are part of the application development methodology, both theoretically and in practice met. Automation tools and methodologies for testing were evaluated. It was considered very important that both methodological solutions and technical support aspects such as: find defects in early stages of development, achieve greater functionality and better coverage during testing, implementation of viable testing cost and time.